Evaluation Of Manpower, Equipment And Quality Control Standards In Peripheral And Intermeiate Laboratories Assessment Checklist Within Seven Selected Provinces In 2011 - Fateme Monjazebi; Rahim Rozbahany; Arezo Memarian; Parisa Farnia (Tehran University of Medical Sciences, 2013)
Background and Aim: Peripheral and intermediate laboratories have an important role in diagnosis, treatment and prevention of tuberculosis. Today, without these laboratories, maintaining health and preventing the spread of tuberculosis is not possible. The aim of this study was Evaluation of manpower, equipment and quality control standards in peripheral and intermediate laboratories assessment checklist within seven selected provinces in year 2011. Materials and Methods: This study was a cross-sectional survey. In this study eighty tow peripheral and intermediate laboratories from seven selected provinces were studied in year 2011. A standardized checklist was used to assess peripheral and intermediate laboratories. Results: The result showed that Esfahan with 20 labs and 8870000 population had the highest number of labs and coverage people between other provinces. Khorasan Razavi with an average of 263 per month has the highest number of admission number and Golestan, with an average of 139 positive cases per month, had the highest number of positive cases between other provinces. In 82 labs 117 laboratory technicians were engaged providing services to patients. Conclusion : The results of this study showed that conditions of most peripheral and intermediate laboratories are optimum and nearly standard. Control and evaluation of peripheral and intermediate laboratories, expert personnel, facilities and equipment are necessary to improve the TB control program in the country.